Gambaran menstruasi atlit basket di SMAN 9 Manado - Tanudjaja, Lia M.; Polii, Hedison; Wungouw, Herlina I. S. (Universitas Sam Ratulangi, 2016)
Abstract: Women or female involved in sport usually become athlete, and athlete usually have high levels of physical exercise, but excess of physical exercise can cause disturbances in female reproductive organ that affects menstrual cycle. Several studies have been conducted to determine the relationship between excess energy consumption due to high level of physical exercise with impaired reproductive function in female athletes such as primary amenorrhea, secondary amenorrhea, and oligomenorrhea. This study aimed to obtain the description of menstruation in female basketball athletes on SMAN 9 Manado. This was a descriptive study using a prospective cross-sectional design. Subjects taken were female students from SMAN 9 Manado who met the inclusion criteria. Instrument that used are physical exercise and menstruation questionnaire. The result showed that 16 subjects had normal menstrual cycle, 12 subjects experienced polymenorrhea, 4 subjects experienced oligomenorrhea, and 1 subject had experienced secondary amenorrhea. Conclusion: Most of the female basketball athletes of SMAN 9 Manado experienced polymenorrhea, some experienced oligomenorrhea, and only one athlete had experienced secondary amenorrhea.Keywords: menstrual disorder, physical exercise, amenorrhea, oligomenorrheaAbstrak: Wanita yang terlibat dalam dunia olahraga banyak yang menjadi atlet sehingga memiliki tingkat latihan fisik yang cukup tinggi. Latihan fisik yang tinggi dapat menyebabkan gangguan pada wanita, diantaranya dapat menimbulkan gangguan pada siklus menstruasi. Beberapa penelitian telah dilakukan untuk mengetahui hubungan antara pemakaian energi berlebih akibat latihan fisik yang tinggi dengan timbulnya gangguan fungsi reproduksi pada atlet wanita berupa amenorea primer, sekunder, dan oligomenorea. Tujuan penelitian ini untuk mengetahui gambaran menstruasi pada atlet basket siswi di SMAN 9 Manado. Metode penelitian ini deskriptif prospektif dengan desain potong lintang. Subjek penelitian ialah siswi-siswi SMAN 9 Manado yang memenuhi kriteria inklusi. Instrumen yang digunakan ialah kuesioner latihan fisik dan menstruasi. Hasil penelitian didapatkan 16 subjek memiliki siklus haid normal, 12 subjek mengalami polimenorea, 4 subjek mengalami oligomenorea, dan 1 subjek pernah mengalami amenorea sekunder. Simpulan: Sebagian besar atlet basket di SMAN 9 Manado mengalami polimenorea, beberapa mengalami oligomenorea, dan hanya 1 atlit yang pernah mengalami amenorea sekunder.Kata kunci: gangguan menstruasi, latihan fisik, amenorea, oligomenorea.